Structure and properties of cork-silica Xerogel nanocomposites: influence of the cork content - Garcia, Ana (2020)
Environmentally friendly nanocomposites were synthesized from a silica precursor and cork under mild conditions and dried at atmospheric pressure. Because of the covalent bonding between the components, these CorSil nanocomposites are homogeneous, light (apparent density in the range 360-750 kg m(-3)), machinable, with the Shore D hardness up to 67 and compressive strength up to 22.6 MPa. These properties place them as good replacements for wood, other natural products, and thermoplastic polymers, with the advantage of being flame-retardant. The influence of the cork content and grain size on the structure, porosity, and mechanical properties of the nano composites was studied using infrared spectroscopy, sorption isotherms, compressive strength, and Shore D hardness measurements.